2015
DOI: 10.1038/ismej.2015.150
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic window into carbon metabolism at 3 km depth in Precambrian continental crust

Abstract: Subsurface microbial communities comprise a significant fraction of the global prokaryotic biomass; however, the carbon metabolisms that support the deep biosphere have been relatively unexplored. In order to determine the predominant carbon metabolisms within a 3-km deep fracture fluid system accessed via the Tau Tona gold mine (Witwatersrand Basin, South Africa), metagenomic and thermodynamic analyses were combined. Within our system of study, the energy-conserving reductive acetyl-CoA (Wood-Ljungdahl) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
132
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 57 publications
12
132
3
1
Order By: Relevance
“…Interestingly, YNP_45 and YNP_N21 have near-complete CBB pathways, only lacking two CBB genes: phosphoribulokinase ( prk) and fructose-1,6-bisphosphatase II ( glpX). The ability to fix inorganic carbon opens up a new source of carbon in the deep subsurface, where dissolved organic carbon has been shown to be extremely low 14,15 but inorganic carbon is readily available 16 .…”
Section: Thermoplasma Acidophilum Ferroplasma Acidarmanus Fer1mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, YNP_45 and YNP_N21 have near-complete CBB pathways, only lacking two CBB genes: phosphoribulokinase ( prk) and fructose-1,6-bisphosphatase II ( glpX). The ability to fix inorganic carbon opens up a new source of carbon in the deep subsurface, where dissolved organic carbon has been shown to be extremely low 14,15 but inorganic carbon is readily available 16 .…”
Section: Thermoplasma Acidophilum Ferroplasma Acidarmanus Fer1mentioning
confidence: 99%
“…It is therefore likely to occur widely in sediments and the subsurface. It has been estimated that after sulphate reduction, CO oxidation is the most energetically favourable anaerobic reaction in the deep terrestrial subsurface 15 . In addition to carbon monoxide (cox) genes, the YNP_45 Hadesarchaea bin also has distinct genes for catalytic nickel-containing CO dehydrogenase (CooS) and the iron sulphur subunits (CooF), suggesting that they are able to oxidize CO and H 2 O to CO 2 and H 2 as an energy source.…”
Section: Thermoplasma Acidophilum Ferroplasma Acidarmanus Fer1mentioning
confidence: 99%
“…Methanogens and sulfate reducers, and the respective energy processes, are thought to be the dominant players and have been the research foci. Recent investigations showed that, in some deep, fluid-filled fractures in the Witwatersrand Basin, South Africa, methanogens contribute <5% of the total DNA and appear to produce sufficient CH 4 to support the rest of the diverse community. This paradoxical situation reflects our lack of knowledge about the in situ metabolic diversity and the overall ecological trophic structure of SLiMEs.…”
mentioning
confidence: 99%
“…Whereas heterotrophs use dissolved organic carbon (DOC) transported from the surface and/or produced in situ, detrital organic deposits buried along with the sediments, and hydrocarbons migrating into petroleum reservoirs, chemolithoautotrophs fix dissolved inorganic carbon (DIC). In oligotrophic systems, subsurface lithoautotrophic microbial ecosystems (SLiMEs) (1) that are fueled by H 2 support the occurrence of autotrophic methanogens, acetogens, and sulfate reducers (2)(3)(4)(5). These environments can host highly diverse communities, consisting mostly of prokaryotes, but also multicellular microeukaryotes and viral particles (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…However, scientific knowledge of these micro-organisms remains very limited due to the difficulties in accessing these environments and our inability to isolate the indigenous microbiota through traditional cultivation techniques (Colwell & D'Hondt, 2013). Molecular ecology studies of deep subsurface habitats have revealed the presence of micro-organisms of nearly all currently identified bacterial and archaeal phyla, both cultivated and uncultivated (candidate divisions) (Takai et al, 2001;Inagaki et al, 2003;Gihring et al, 2006), and recent studies have suggested that Firmicutes and Proteobacteria are the predominant phyla in many subterranean communities (Itavaara et al, 2011;Blanco et al, 2014;Magnabosco et al, 2016). Here we describe a novel species of phylum Firmicutes-Tepidibacillus infernus strain MBL-TLP T , isolated from a microbial mat sample of a 3540-m-deep layer of the TauTona gold mine, one of the deepest mines in the world.…”
mentioning
confidence: 99%